Being Explicit about the Moral Purpose of Primary Geography - Catling, Simon (Journal of Geography Education, 2024)
The moral dimension of primary geography in England is less obvious in the current national curriculum requirements for geography. The debate about geography and powerful knowledge has dominated in recent years, and has limited consideration of morality in geography. As a result, primary school geography curriculum statements focus on the knowledge (and skills) to be learned, leaving the moral dimension often unstated and implicit. The view in this article is that the moral dimension in primary geography is important and cannot be neglected. Primary schools need to make clear in their geography curriculum statements the moral aspects (or values) which they espouse in the subject to ensure these are clear to all who have a stake in the school's geography curriculum.
Keywords: primary geography, school geography statements, stating geography's morality explicitly, values in primary geography